Migratory mobility and drug trafficking. Exclusion and poverty as spaces of convergence - Urbano Reyes, Javier (Política, Globalidad y Ciudadanía, 2021)
The purpose of this article is to identify those processes that converge as common roots in the interaction and strengthening of drug trafficking and migratory mobility. These two issues were not born in contemporary times, but they do acquire the characteristics and socioeconomic impact on the system of nations at the same time as the reaffirmation of the consequences of the current economic model. The aim is to recognize, through those directly affected, the impact of these two phenomena on the weakening of the social fabric at the same time as the consolidation of actors parallel to the State, who to a large extent become social competitors of State public policy, hence the need to propose strategies for managing these two problems from an integral perspective, under the premise that attention to one issue must run parallel to the management of the other, as synergistic and not dissociated phenomena. To this end, a qualitative analysis based on the search for documentary sources and statistics on migratory mobility and poverty, among others, has been used as a starting point, along with the organization and systematization of life testimonies, which give support and a relevant role to the experience of the actors